2019
DOI: 10.1002/ams2.395
|View full text |Cite
|
Sign up to set email alerts
|

Unique characteristics of frequent presenters to the emergency department in a Japanese population: a retrospective analysis

Abstract: Aim Little evidence on Japanese frequent presenters (FPs) is available. Therefore, this retrospective cohort study compared characteristics between FPs and non‐frequent presenters (NFPs) in emergency departments (EDs) in Japan. Methods Frequent presenters included those who presented to an ED ≥4 times during the study period from August 1, 2012 to July 21, 2013. The primary outcomes were triage level and disposition. Secondary outcomes were ED length of stay, method of arrival, and discharge diagnosis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…In the previous study conducted in Japan, mental health issues were not related to frequent ED visits but this may be attributable to the absence of full-time psychiatric providers in that hospital. 11 While a difference was noted in the proportion of frequent ED visits for paediatric problems between the secondary and tertiary hospital, this finding was not surprising given the lack of a full-time paediatrician in the secondary hospital in our study. Because characteristics of frequent ED users are heterogeneous, 7 analysis of characteristics of frequent ED users in each hospital is important to reduce frequent ED visits.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…In the previous study conducted in Japan, mental health issues were not related to frequent ED visits but this may be attributable to the absence of full-time psychiatric providers in that hospital. 11 While a difference was noted in the proportion of frequent ED visits for paediatric problems between the secondary and tertiary hospital, this finding was not surprising given the lack of a full-time paediatrician in the secondary hospital in our study. Because characteristics of frequent ED users are heterogeneous, 7 analysis of characteristics of frequent ED users in each hospital is important to reduce frequent ED visits.…”
Section: Discussionmentioning
confidence: 46%
“…These findings contrast with the previous Japanese study conducted near Tokyo where 1.39% frequent ED users (≥4 visits/year) occupied 6.75% of all ED visits and the previous study did not report the used healthcare expenditures. 11 The differences may be attributable to a different setting as the latter is from an ED in a single tertiary hospital serving a population of 170 000 near metropolitan Tokyo. Because this tertiary hospital was located near a metropolitan area, the patients might visit the hospital from a wider range of areas compared with the present study’s setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, studies have focused on specific conditions, such as bronchial asthma and psychiatric disorders, but there are few studies regarding the association of other factors and ED visitation frequency. A study by Takeuchi et al indicated that patients receiving public medical assistance had a higher risk of frequently visiting the ED than did patients using regular medical insurance in Japan 11 , but that study did not take age or underlying conditions into account.…”
Section: Introductionmentioning
confidence: 99%